Acute Phase Treatment Outcomes of Electroconvulsive Therapy in Adolescents and Young Adults. Issue 3 (September 2019) - Benson, Nicole M.; Seiner, Stephen J.; Bolton, Paula; Fitzmaurice, Garrett; Meisner, Robert C.; Pierce, Casey; Busch, Alisa B.
Abstract : Objective: Electroconvulsive therapy (ECT) is a highly efficacious, well-tolerated treatment in adults. Little is known, however, about its effectiveness in adolescents and young adults. Our objectives were to assess clinical outcomes after acute phase ECT in adolescents and young adults and determine whether screening positive or negative for a substance use disorder (SUD) is associated with differences in treatment outcomes. Methods: Study sample consisted of all patients 16 to 25 years old who received ECT from May 2011 to August 2016 and who completed self-reported SUD screens and the Behavior and Symptom Identification Scale-24 (BASIS-24) initially and completed the BASIS-24 again after the fifth ECT treatment. For 5 BASIS-24 domains, longitudinal changes in mean domain scores were assessed; mean changes by SUD screening status were also examined using linear mixed models. Results: One hundred ninety adolescents and young adults, with mean age 21.0 ± 2.6 years, met inclusion criteria. Electroconvulsive therapy was associated with significant clinical improvement (score decreases) in all 5 BASIS-24 domains during the acute phase treatment ( P < 0.001). Sixty-four percent (122/190) screened positive for SUD. Compared with adolescents and young adults screening negative for SUD, those screening positive for co-occurring SUD had greater improvement in depression/functioning (−0.37 ± 0.14, P = 0.009), interpersonal relationships (−0.27 ± 0.13, P = 0.045), and emotional lability (−0.27 ± 0.14, P = 0.044) domains after the fifth ECT treatment. Conclusions: Electroconvulsive therapy in adolescents and young adults was associated with significantly improved clinical outcomes during acute phase treatment. Adolescents and young adults screening positive for SUD had better acute phase ECT outcomes in self-reported depression/functioning, interpersonal relationships, and emotional lability than those screening negative. More research is needed to clarify adolescents and young adult patient characteristics that may be associated with differential ECT outcomes.